Influence of hair loss syndrome on black‐tailed deer fawn survival. Issue 7 (September 2014) - McCoy, Robert H.; Murphie, Shannon L.; Szykman Gunther, Micaela; Murphie, Bryan L.
ABSTRACT Recent declines in black‐tailed deer (Odocoileus hemionus columbianus) populations in Washington have been attributed partly to low recruitment. However, sparse information exists regarding fawn survival and factors affecting recruitment. During 2006–2009, we captured 228 fawns on the Olympic Peninsula, Washington, USA, to determine sources of fawn mortality, estimate survival rates, identify factors influencing survival rates, assess the influence of hair loss syndrome (HLS) on winter survival, and estimate population growth. We used known fate modeling in Program MARK to estimate survival rates to age 50 weeks and to 9 weeks by developing 2 candidate a priori model sets. We recorded 129 mortalities; predation was the leading cause (74%). Mountain lions (Puma concolor) and bobcats (Lynx rufus) were the most common predators. The survival rate to 50 weeks was 0.33 (95% CI = 0.24–0.43); survival differed between capture years and was age dependent, with fawns being most vulnerable to mortality during the first 9 weeks then again during the winter. The survival rate to 9 weeks was 0.65 (95% CI = 0.60–0.68), and our results suggested that an interaction between age and birth mass influenced survival. A posteriori modeling indicated that greater body mass and earlier birth date also influenced survival over the first 9 weeks of life. Fawns afflicted with HLS had lower survival rates than non‐afflicted fawns (P = 0.018) during winter. Poor body condition, based on femur marrow assessment, was a factor in 89% of fawns that died over winter. We estimated the growth of the population to be stationary at λ = 1.0. Estimates of lambda increased 3% when survival was modified to assume HLS was not a factor. We conclude that fawn mortality during the first 9 weeks followed by a significant increase in winter mortality, exacerbated by HLS, combine to limit black‐tailed deer population growth. Inherent nutritional limitations in summer forage may have influenced survival of many fawns, pre‐disposing them to mortality during the summer and winter. Wildlife managers can use this information to improve population modeling and management of black‐tailed deer populations afflicted with HLS. © 2014 The Wildlife Society.